ALOKASI CURAHAN TENAGA KERJA KELUARGA USAHA TERNAK SAPI POTONG DI KECAMATAN WONOSARI KABUPATEN GUNUNGKIDUL - , Fisca M. Soumokil ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Family cattle farming mostly depend on family member as source of labour. The purpose of this research was to study labour time allocation within Family cattle farm and factors affecting it. Cattle herders in Wonosari district Gunungkidul regency who have been rearing cattle for at least one year were participated in the research. Sample of villages were taken by using purposive sampling based on the highest number of cattle ownership. Fifteen respondents for each village were selected using quota sampling. The respondents within a village were chosen using convenience sampling. Multiple-regression analysis was applied to analyze factors affecting labor time allocation The results showed that average labour allocation in family cattle farm was 2459,43 men labour/year. The largest labour time (1255.96 men labour/year) was allocated to cut grass. From the largest to less, number of hours allocated to different cattle farming activities were as follows: to cut grass (1255.96 men labour/year), to feed the cattle (684.74 men labour/year), to clean the stall (159.39 men labour/year), to manage fodder areal (7.3 men labor/year), to cure disease (5.84 men labour/year) and other farm activity (4.915 men labour/year). The findings revealed that there was positive effect of family labor time allocation on two aspects: land size and farm size. Reversely, negative affect was shown on age of the farm owner.